Linking Software Development and Business Strategy through Measurement. - Basili, Victor R.; Lindvall, Mikael; Regardie, Myrna; Seaman, Carolyn; Heidrich, Jens; Münch, Jürgen; Rombach, Dieter; Trendowicz, Adam (Computer (00189162), 2010)
The article focuses on the GQM*Stragies approach in software development and business strategy. It notes that goal-oriented approaches in measurement programs provide a method for an organization or project to define its goals and refine it into specifications of data to be collected. The approach aims to provide links among organizational levels and flexibility to tailor the approach to an organizations specific needs and objectives. It also provides a scenario in using the GQM*Strategies in software and business development.